2017
DOI: 10.1038/s41598-017-08155-y
|View full text |Cite
|
Sign up to set email alerts
|

The white gene controls copulation success in Drosophila melanogaster

Abstract: Characteristics of male courtship behavior in Drosophila melanogaster have been well-described, but the genetic basis of male-female copulation is largely unknown. Here we show that the white (w) gene, a classical gene for eye color, is associated with copulation success. 82.5% of wild-type Canton-S flies copulated within 60 minutes in circular arenas, whereas few white-eyed mutants mated successfully. The w + allele exchanged to the X chromosome or duplicated to the Y chromosome in the white-eyed genetic back… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 62 publications
1
32
3
Order By: Relevance
“…The white ( w ) mutant flies are known to show longer copulation latency (time until copulation initiation) than wild‐type flies (Xiao et al. ). However, the effects on copulation duration or mobility during copulation (the traits of our interest in the present study) have not been reported, and as all our tested introgression lines had the same w mutant background, this mutation likely had little effect on our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The white ( w ) mutant flies are known to show longer copulation latency (time until copulation initiation) than wild‐type flies (Xiao et al. ). However, the effects on copulation duration or mobility during copulation (the traits of our interest in the present study) have not been reported, and as all our tested introgression lines had the same w mutant background, this mutation likely had little effect on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that ectopic w + insertions accompanying the construction of transgenes can rescue the effect on copulation latency (Xiao et al. ) as well as enhance male−male courtship behavior (Zhang and Odenwald ; Hing and Carlson ). However, the effects on copulation duration or mobility are not known.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, White transports second messengers and many small molecules (Sullivan et al ., ; Evans et al ., ). Consequently, previous researchers have proposed that this gene may influence a range of behavioural and physiological pathways in insects, such as phototactic personality (Kain et al ., ), courtship and mating (Zhang and Odenwald, ; Anaka et al ., ; Dimitrije et al ., ; Xiao et al ., ;), learning (Diegelmann et al ., ) and hypersensitivity to ethanol (Chan et al ., ). In the noctuid moth Helicoverpa armigera , homozygous white knockouts were lethal in the embryo (Khan et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because although biologically functional, white-eyed Drosophila suffer from a series of neurological disadvantages other than poor vision due to their malfunctioning white protein. These include reduced spatial memory [50], low copulation success [41] and progressive locomotor deficiencies [42]. For this reason, care should be taken when interpreting results from behavioral tests using these (and other) mutants, and it seems reasonable to expect that handling would negatively affect white-eyed flies more.…”
Section: Discussionmentioning
confidence: 99%